2020
DOI: 10.1021/acs.jpcc.9b09586
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Molybdenum(VI) and Tungsten(VI) Oxide Species on Partly Dehydroxylated Silica: A Computational Perspective

Abstract: Although silica-supported molybdenum and tungsten oxide systems are widely used in catalysis, the nature of the surface metal oxide species is still not fully recognized. In this work, comprehensive periodic and cluster density functional theory (DFT) studies of the isolated Mo­(VI) and W­(VI) oxide species on dehydrated amorphous silica have been performed to give insight into their heterogeneity. It is shown that the relative stabilities of the metal oxide species strongly depend on their location that influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 66 publications
(259 reference statements)
3
28
0
Order By: Relevance
“…The bands in the range 2924 cm −1 and 1445 cm −1 can be ascribed to the stretching and bending vibrations of N-H of NH4 + groups which are well consistent with the previous report in literature [21]. The peaks at 974 cm −1 and 919 cm −1 are ascribed to the oxygen symmetry stretching mode of Mo=O [22]. The bands in the range 574 cm…”
Section: Ftir Spectral Studiessupporting
confidence: 90%
“…The bands in the range 2924 cm −1 and 1445 cm −1 can be ascribed to the stretching and bending vibrations of N-H of NH4 + groups which are well consistent with the previous report in literature [21]. The peaks at 974 cm −1 and 919 cm −1 are ascribed to the oxygen symmetry stretching mode of Mo=O [22]. The bands in the range 574 cm…”
Section: Ftir Spectral Studiessupporting
confidence: 90%
“…The value of ∠Mo–O–Si is a strong function of the molybdasiloxane ring size. DFT simulations show that grafted molybdates have smaller Mo–O–Si angles (<138°) when the Mo atom is part of a 6-membered (MoSi 2 O 3 ) ring. , The high fraction of vicinal silanols present on partially dehydroxylated amorphous silicas could result in a large fraction of these smaller molybdasiloxane rings, which contribute little to the peak intensity at 2.9 Å. , …”
Section: Resultsmentioning
confidence: 99%
“…At lower Mo loadings, four-coordinate monomeric Mo(O) 2 (OSi) 2 sites (Scheme a) are proposed to dominate the site distribution , and are inferred to be the immediate precursors of the active sites. They often serve as a starting point for computational modeling of supported Mo catalysts. , An alternate monomeric structure, the five-coordinate Mo­(O)­(OSi) 4 site in Scheme b, was also proposed in silica-supported catalysts on the basis of the Raman and UV–vis spectroscopic assignments. Both monomeric structures have analogues in well-characterized molecular molybdenum oxoalkoxides (Scheme e). However, a computational study suggested that formation of supported Mo­(O)­(OSi) 4 on partially dehydroxylated silica is unlikely because the density of hydroxyl groups is rarely high enough to generate four closely co-located Mo–O–Si linkages …”
Section: Introductionmentioning
confidence: 99%
“…PW91 exchange-correlation functional is used as model used herein are adapted from prior models of supported WO x catalysts published in the literature. 25,31,32 The valence electrons are treated explicitly and their interactions with the ionic cores are described by the Projector Augmented-Wave method (PAW), which allows using low energy cut off equal to 400 eV for the plane-wave basis. A sampling of the Brillouin zone with 2 × 2 × 1 mesh was applied for all models in this work.…”
Section: Methodsmentioning
confidence: 99%